International Law - Wilson, George Grafton, 1863-1951; Tucker, George Fox, 1852-1929 (Salt Lake City, UT : Project Gutenberg, 2013)
"International Law" by George Grafton Wilson and George Fox Tucker is a scientific publication written in the early 20th century. This work serves as a comprehensive introduction to the principles and practices of international law, emphasizing its growing significance due to increased global interaction and diplomacy. It covers a wide range of topics, from the historical roots and definitions of international law to the rights and obligations of states. The opening of the book begins with a preface explaining the authors' goal to provide a concise introduction to international law, which they believe has become more crucial in light of expanding international negotiations. They note that the text relies on established cases and codes to illustrate key principles, while also preparing appendices for easy reference to supporting materials. The initial chapters introduce foundational concepts, such as the definition of international law, its divisions into public and private law, and its historical development, outlining how these elements interplay within the context of states' relationships and interactions. (This is an automatically generated summary.)
Release date is 2013-01-02
E-text prepared by Carl Hudkins, Heike Leichsenring, jnik
Keywords: International law